A low-complexity joint detection-decoding algorithm for nonbinary LDPC-coded modulation systems - Xuepeng Wang; Baoming Bai; Xiao Ma (2010 IEEE International Symposium on Information Theory, 2010)
In this paper, we present a low-complexity joint detection-decoding algorithm for nonbinary LDPC coded-modulation systems. The algorithm combines hard-decision decoding using the message-passing strategy with the signal detector in an iterative manner. It requires low computational complexity, offers good system performance and has a fast rate of decoding convergence. Compared to the q-ary sum-product algorithm (QSPA), it provides an attractive candidate for practical applications of q-ary LDPC codes.